2019
DOI: 10.1111/1365-2664.13389
|View full text |Cite
|
Sign up to set email alerts
|

A functional diversity approach of crop sequences reveals that weed diversity and abundance show different responses to environmental variability

Abstract: 1.Combining several crop species and associated agricultural practices in a crop sequence has the potential to control weed abundance while promoting weed diversity in arable fields. However, how the variability in environmental conditions that arise from crop sequences affects weed diversity and abundance remains poorly understood, with most studies to-date simply opposing weed communities in monoculture and in crop rotation. Here, we describe crop sequences along gradients of disturbance and resource variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…The different long-term farming systems, under the same crop rotation sequence and tillage practices, resulted in significant differences in the seedbank weed community. Although previous studies pointed out to a strong influence of crop rotation and tillage on weed communities (Mahaut, Gaba, & Fried, 2019), here we found that other farming practices determined significant differences in the abundance, diversity and floristic composition of the weed seedbank, as well as in the functional diversity, redundancy and composition. Besides, we found that not only long-term farming but also the yearly management associated to the last crop sown were important determinants of the functional and species composition of the soil seedbank.…”
Section: Discussioncontrasting
confidence: 79%
“…The different long-term farming systems, under the same crop rotation sequence and tillage practices, resulted in significant differences in the seedbank weed community. Although previous studies pointed out to a strong influence of crop rotation and tillage on weed communities (Mahaut, Gaba, & Fried, 2019), here we found that other farming practices determined significant differences in the abundance, diversity and floristic composition of the weed seedbank, as well as in the functional diversity, redundancy and composition. Besides, we found that not only long-term farming but also the yearly management associated to the last crop sown were important determinants of the functional and species composition of the soil seedbank.…”
Section: Discussioncontrasting
confidence: 79%
“…The trait‐based approach allows for the comparison of various cropping systems involving different crop and spontaneous species (Mahaut et al 2019), using continuums of trait variations as explanatory or predictive variables for agroecosystem services (Duarte et al 1995, Mouquet 2015). It seems therefore important to multiply trait‐based experiments involving ITV in various agrosystems to assess their potential to provide ecosystem services (Martin and Isaac 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in disturbance timing, as reflected in crop sowing and harvest dates, and in functional attributes of crops, such as height and competitive ability for light, are important determinants of cropping system effects on weeds, and may have stronger effects than crop species richness per se Mahaut et al, (2019). examined data from 473 fields in France collected over five consecutive seasons and found that when evaluated over multiple phases of the rota-…”
mentioning
confidence: 99%